PERKEMBANGAN BAHASA DAN SOSIAL PADA FASE ANAK USIA SEKOLAH - Helen Suhasri, Anugerah; Juli Astuti, Noni; ., Abdurrahmansyah (Inspiratif Pendidikan, 2023)
Development is a process in every growth in an individual child. Its initial development shows a change according to the age of the child. in every change it is hoped that it will show an ideal development process like in other child growth periods. So that not a few parents are worried about the growth and development of children, especially at the vulnerable age of 6-12 years. Because at this age children will experience a process of development that looks active in their daily life. There are approximately seven developmental phases experienced by elementary school age children, but this study aims to determine the language and social development of elementary school age children. The type of research used is a literature study with a qualitative research approach. And there are two kinds of data sources used to write this article, namely primary data sources and secondary data sources. Primary data sources, the authors use primary journal references in writing articles, namely Latifa's journal on Aspects of Development in Elementary School Children and secondary data sources the authors use from various journals and other books that contain material related to language and social development in the elementary school age phase of children. The findings in this study indicate that children develop rapidly at elementary school age, namely language and social development. This development is not the same from one child to another. Many factors can influence these developments, including factors in the family environment and school environment. With the existence of research on this development, it can be used as a reference for teachers to carry out learning in schools and to see problems that occur in schools. Thus it can be a solution for teachers to overcome problems in learning and child development.